Growth and Bone Mineral Density Changes in Ovariectomized Rats Treated with Estrogen Receptor Alpha or Beta Agonists - Kang, Byung Ho (J Korean Med Sci, 2020)
BACKGROUND: Estrogen controls the pubertal growth spurt, growth plate closure, and accretion of bone mineral density (BMD) of long bones after biding estrogen receptor (ER). There are two subtypes of ER, ERα and ERβ. If each ER subtype has different effects, we may control those actions by manipulating the estrogen binding intensity to each ER subtype and increase the final adult height without markedly reducing BMD or impairing reproductive functions. The purpose of our study was to compare these effects of ERα and ERβ on long bones in ovariectomized rats. METHODS: Thirty female rats were ovariectomized and randomly divided into 3 groups. The control, propylpyrazole triol (PPT), and 2,3-bis (4-hydroxyphenyl) propionitrile (DPN) groups were subcutaneously injected for 5 weeks with sesame oil, PPT as an ERα agonist, and DPN as an ERβ agonist, respectively. The crown-lump length and body weight were measured weekly. BMD, serum levels of growth hormone (GH) and estradiol were checked before and after 5 weeks of injections. Pituitary GH1 expression levels were determined with quantitative real-time polymerase chain reaction, the proximal tibias were dissected, decalcified and stained with hematoxylin-eosin, and the thicknesses of epiphyseal plates including proliferative and hypertrophic zones were measured in 20-evenly divided sites after 5 weeks of injections. Comparisons for auxological data, serum hormone and pituitary GH1 expression levels, BMD, and epiphyseal plate thicknesses among 3 groups before and after injections were conducted. RESULTS: There was no significant difference in body lengths among 3 groups. The body weights were significantly lower, but, serum GH, pituitary GH1 expression levels, and BMDs were higher in PPT group than the other 2 groups after 5 weeks of injections. There was no significant difference in the thicknesses of the total epiphyseal plate, proliferative, and hypertrophic zone among 3 groups. CONCLUSION: ERα is more involved in pituitary GH secretion and bone mineral deposition than ERβ. Weight gain might be prevented with the ERα agonist.